1990
DOI: 10.1104/pp.92.1.242
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Regulates Cell Wall Extensibility in Wheat (Triticum aestivum L.)

Abstract: Mutations (Rht genes) blocking sensitivity to gibberellic acid (GA) were used to examine phytohormone mediated cell wall expansion in wheat (Triticum aestivum L.). Irreversible extensibility of immature leaf segments, as determined by stress/strain (instron) measurements, declined with Rht gene dose. Exogenous GA3 significantly increased wall extensibility in the nonmutant controls but had no effect on the near-isogenic GA-insensitive genotypes. Furthermore, ancymidol, an inhibitor of gibberellin biosynthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…In longer-term experiments with rht (tall) wheat grown at 22 ~ C, applied GA3 increased wall extensibility in the leaf elongation zone (Keyes et al 1990) indicating that, even under these conditions, endogenous GAs may constrain the rate of leaf expansion. In the present experiments, the absolute responsiveness of the rht3 line to applied GA~ was greater at 10 ~ C than at 20 ~ C and, since endogenous GAt (plus GA3) content was similar, it seems reasonable to conclude that endogenous GAs may be more sensitive regulators of leaf expansion at lower than at higher temperatures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In longer-term experiments with rht (tall) wheat grown at 22 ~ C, applied GA3 increased wall extensibility in the leaf elongation zone (Keyes et al 1990) indicating that, even under these conditions, endogenous GAs may constrain the rate of leaf expansion. In the present experiments, the absolute responsiveness of the rht3 line to applied GA~ was greater at 10 ~ C than at 20 ~ C and, since endogenous GAt (plus GA3) content was similar, it seems reasonable to conclude that endogenous GAs may be more sensitive regulators of leaf expansion at lower than at higher temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…In a separate study with wheat lines grown at 18-20 ~ C, both epidermal cell length and the rate of leaf expansion were proportional to the dosage of Rhtl and Rht2 semidwarfing alleles (Keyes et al 1989). Irreversible extensibility of immature leaf segments also declined with increasing Rht gene dose and was correlated positively with mature sheath length (Keyes et al 1990). It was reported recently that the more potent Rht3 dwarfing gene caused a reduction in both epidermal cell length and cell number per leaf (Hoogendoorn et al 1990).…”
Section: Introductionmentioning
confidence: 95%
“…For example, Stoddart & Lloyd (1986) found that, in wheat meristems, the minimum temperature for cell expansion was lowered by direct applications of GAg, and Keyes, Sorrells & Setter (1990), with the aid of dwarf mutants of wheat, showed that GA was involved in determining the extensibility of leaf sheath cells. The higher rates of cell and leaf extension in long days can, therefore, be interpreted in terms of increased cell wall extensibility along the long axis of the leaf, although it is possible that the yield threshold pressure could also be affected (Tyree & Jarvis, 1982).…”
Section: The Role Of Gibberellins In the Photoperiodic Stimulationmentioning
confidence: 99%
“…The phytohormone GA also participates in stem elongation and wall extensibility in plants [27] but whether the induction of the (i---)3,1--)4)-fl-gluc~_nase isoenzyme El gene by GA3 in young leaves (Fig. 1) is related to this effect remains unknown.…”
Section: Discussionmentioning
confidence: 99%